Insight into the stickiness of faecal sludge from dry sanitation technologies: a path toward sustainable and efficient FSM via thermal processes - Mupinga, Ratidzaishe T.; Mercer, Edwina; Rayavellore Suryakumar, A.; Pocock, Jonathan; Septien, Santiago (Elsevier, 2025)
This study explores the stickiness behaviour of faecal sludge (FS) during thermal drying—an operational challenge that hampers the performance of faecal sludge management (FSM) systems. Samples were collected from ventilated improved pit (VIP) latrines and urine diversion dry toilets (UDDTs) in Durban, South Africa, and analysed using a texture analyser to measure adhesive and cohesive forces over a temperature range of 25–80 °C and moisture contents between 20–90 wt.%. Complementary tests were conducted to assess water activity, drying kinetics, rheological properties, and plastic behaviour. Maximum stickiness occurred in the 50–60 wt.% moisture range. In this region, FS transitioned from a viscoelastic fluid to lumpy and plastic consistency dominated by interstitial moisture, and eventually to a granular solid at the end of the sticky region, as interstitial water was depleted. The sticky phase coincided with the transition from the first to the second falling-rate period of drying, reflecting a shift from surface to internal moisture evaporation. Cohesive forces were consistently greater than adhesive forces and increased modestly at 80 °C. UDDT sludge was slightly stickier than VIP sludge under similar conditions. The results highlight the strong dependence of FS stickiness on moisture content and its binding properties. To address this issue, the study proposes mitigation strategies such as bypassing the sticky range, using bulking agents, or applying pre-treatments to improve drying performance. These findings provide practical guidance for the design and operation of sludge treatment systems and contribute to more sustainable FSM practices.
Keywords: 4004 Chemical Engineering; 40 Engineering; 40 Engineering; Adhesion; Cohesion; Thermal drying; Plastic limit; Bound moisture; Rheology